EFEKTIVITAS EKSTRAK ETANOL DAUN Tagetes erecta L. TERHADAP MORTALITAS LARVA DAN IMAGO SERANGGA VEKTOR DEMAM BERDARAH Aedes aegypti L. - , TRISNA RAHMAH, Dr. Siti Sumarmi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Aedes aegypti L. is a primary vector of dengue virus which causes dengue hemorrhagic fever (DHF) disease. The countermeasure against DHF disease is done by disruptingthe life cycle of Ae. aegypti. The use of synthetic chemicals to control Ae. aegypti has negative effects on the human health, environment and the resistance of Ae. Aegypti to synthetic insecticides. The use of natural insecticides made from active substance of plants is a way to reduce the negative effects resulted from the use of synthetic insecticides. Tagetes erecta L. is one of the plants that contains active compounds of terpenoid, flavonoid, saponin and tanin which can be used as insecticides. The aim of this study is to elucidate the effectiveness and the effective concentration of ethanol extract of T. erecta leaves on larva and imago of Ae. aegypti. The research was conducted by using Completely Randomized Design with 7 treatments and triplicate. Each treatment used 10 of the fourth instar larvae and 10 imago of Ae. aegypti. The deaths of larvae and imago of Ae. aegypti were accounted at 24 hours after the testing and then were analyzed by using Probit Analysis to determine the LC50 and LC90 of 24 hours of the ethanol extract of T. erecta leaves on the larvae and imago. The effects of concentration of the extract on the death of the larvae and imago were analyzed by using Anova with the use of SPSS 16 software. The result of this study showed that the average death of Ae. aegypti larvae at 1000 ppm was 86,7% which occurred at the fifth hours after the exposure. The average death of Ae. aegypti larvae of 100 % was achieved at the second hours after the exposure of 2000 ppm. The average deaths of Ae. aegypti larvae at 24 hours after the exposureof 1000 and 1500 ppm were 93,3% and 100 %, respectively. The LC50 and LC90 of 24 hours of the extract on larvae were 568,50 ppm dan 1465,40 ppm, respectively.The effective average of death of the imago was occurred at the concentration of 5000 ppm (90 %), the average of death of 100 % was achieved at 7000 ppm. LC50 and LC90 of 24 hours of the extract on the imago were 2945,31 ppm dan 5594,31 ppm, respectively. This study demonstrated that ethanol extract of T. erecta leaves is more effective in killing the fourth instar larvae than imago of Ae. aegypti. The ethanol extract of T. erecta leaves has significant impact on the death of larvae and imago of Ae. aegypti, p < 0,05.